Laser tattoo removal comparison between 1064 and 532 NM of a Q-switched ND:YAG laser treatment - Almabrouk Imrigha, N. A. (Penerbit UTM Press, 2016)
Invention of the Q-switch advanced laser method is the most effective methods of tattoo removal compared to other methods of i.e. chemical, mechanical and surgical. In this study, we are reporting black pigment tattoo removal by comparing two wavelengths 532 nm and 1064 nm of Q-switched Nd-YAG laser. Using a single-pulse laser at 1064 nm wavelength, the maximum laser fluence for skin damage is 3.04 J/cm2 with pulse energy 0.55 J. While, at 532 nm wavelength, maximum laser fluence is 0.5 J/cm2 with pulse energy 0.42 J at 8-10 ns for tattooed skins. Moreover, after 1064 nm and 532 nm laser irradiations, skin biopsy of black tattooed rat’s skin demonstrates the ink granules local redistribution. Microscopic study indicates that black ink particles become smaller and vanished from the skins after 1064 nm laser treatment. The findings of this study indicate that 1064 nm wavelengths of Q-switched Nd-YAG laser treatment with 0.55 J pulse energy, is one of the significant methods of black tattoo removal with remarkable differences.